Anatomy-Zoology building - Unidentified photographer (Colorado State University. Libraries, 1972)
Photo and caption of new Anatomy-Zoology Building, 60% complete. CSU Comments, March 23, 1972.
Not digitized by CSUL Digital Services.
Keywords: anatomy-zoology; anatomy; zoology